PENINGKATAN KESEHATAN MASYARAKAT DI DUSUN NGLAMPU DENGAN PALANG DAPUR - Madita, Vincentia Ganesi; Sitio, Jessica Christy; Octavianus, Agatha Riona (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2014)
Dusun Nglampu is located in Desa Pucanganom, Kecamatan Srumbung, Kabupaten Magelang. People have difficulty to access health service because of expensive medication in hospital and limited operation time in puskesmas. Commonly, people do not know how to process herbs for medication. Consequently, they do not have alternative medication which is accessible. In this program, a guideline of the use of herbs as medicine is packed in a book called "Palang Dapur" which provides information about disease and its symptoms, herbs that can be used to solve the symptoms; about methods to prepare the herbs; how to consume, and other relevant advices. There are 20 diseases and symptoms that are discussed in the "Palang Dapur", i.e.: cough, nausea, vomiting, diarrhea, fever, skin diseases, itching, cholesterol, rheumatoid arthritis, hypertension, irregular menstruation, abdominal pain due to menstruation, vaginal discharge, toothache because of caries, fatigue, aches, burns, acne, insomnia, headache, and pain eyes. Counseling and mentoring related to the use of the "Palang Dapur" were done. This resulted in increasing peopleâs knowledge and skills in using herbs as herbal medicines. Results on pre-test and post-test to demonstrate knowledge and skills of the target communities increased from 52.2% to 93.7%. Results of the questionnaire showed that explaining and sharing of the "Palang Dapur" could increase the use of herbs for medication from 40.9% to 97.7%. Furthermore,, 95% of participants agreed that this program could help to solve their common daily health problems including their family.Key word: herbs, alternative medicine, Palang Dapur, peopleâs knowledge and skill